Transformasi Pelayanan Publik: Implementasi Aplikasi Core Tax dalam Meningkatkan Etika Kepatuhan dan Akuntabilitas Administrasi Perpajakan - Sadam, Muhammad; Araafi, Faathur Al; Munawar, Hilmi Harja; Milliano, Rafael; Ridwan, Ridwan (Peneliti.net, 2025)
Public service transformation is able to create various innovations that can make it easier for users to access existing services. The focus of this research aims to analyze the implementation of Core Tax applications in order to improve compliance ethics and accountability in the tax administration sector. The application of the research approach uses a qualitative method through a descriptive-analytical type of research with the collection of interview data sources, observations, and documentation. From this analysis, the implementation of Core Tax is able to answer various real challenges to the need for innovation in public services, the presence of Core Tax can reflect the government's seriousness in transforming public services through the application of aspects of efficiency, accountability, and compliance ethics. In addition, Core Tax also provides considerable benefits in terms of ease of access to tax payments for taxpayers. However, a number of challenges through the aspects of limited infrastructure, digital literacy, and inadequate bureaucracy are obstacles in the implementation of this application. For this reason, the implementation of Core Tax must strive for synergy between various elements in order to be able to provide a strong commitment in developing accountable and transparent tax services.